Pengelolaan Sampah Anorganik sebagai Media Tanam Microgreen di Pemukiman Warga Lingkar Kampus Universitas Mataram - Rahayu, Rachmawati Noviana; Rohyani, Immy Suci; Ernawati, Ernawati; Isrowati, Isrowati (Jurnal Gema Ngabdi, 2022)
Environmental problems, especially waste problems have become a hot issue. This could be due to the lack of information and learning about the importance of waste management. The more of community residents who live in the circle campus, the more types of waste that will be generated in the surrounding environment. One solution and strategy to reduce waste in the around campus is to manage inorganic waste properly by applying the concept of green lifestyle. The workshop for community consists of three stages, the preparation stage by conducting a site survey making a permit for facilities and infrastructure during the activity, the second stage by holding a workshop with the aim of socializing the inorganic waste management program into a microgreen planting media container that has beneficial and economic value, the last stage is the direct demonstration related to managing inorganic waste into product that have useful and economic value, namely as a container for microgreen planting media. The method used for the workshop activities is Direct Instruction which is carried out to provide an explanation regarding the importance waste management in maintaining the environment. Focus Group Discussion (FGD) which is carried out directly with processing of inorganic waste management. The output of this activity is expected to increase public awareness of environmental problems that have occurred recently, and increase the community who implement a green lifestyle.